2020
DOI: 10.1002/app.49518
|View full text |Cite
|
Sign up to set email alerts
|

Tribological characterization of graphene nanoplatelets/alumina particles filled epoxy hybrid nanocomposites

Abstract: In this work, graphene nanoplatelets have been synthesized using liquid phase exfoliation of graphite flake powder. The exfoliated graphene nanoplatelets were identified and characterized by using UV–Visible–NIR spectroscopy, High resolution transmission electron microscopy, electron diffraction, scanning electron microscopy and X‐ray diffraction. The obtained graphene nanoplatelets and nano alumina at various weight ratios were dispersed in an epoxy matrix to enhance the surface roughness (Ra), micro hardness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…These types of dispersion procedures are required because they promote the dispersion of nanofillers from an agglomerated state to a homogeneous state. The most commonly used dispersion methods are sonication, [ 39,40 ] three roll milling, [ 41 ] planetary mixer, [ 42 ] mechanical stirring and sonication, [ 43 ] magnetic stirring and ball milling [ 44,45 ] and planetary centrifugal mixing and three‐roll milling. [ 46 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of dispersion procedures are required because they promote the dispersion of nanofillers from an agglomerated state to a homogeneous state. The most commonly used dispersion methods are sonication, [ 39,40 ] three roll milling, [ 41 ] planetary mixer, [ 42 ] mechanical stirring and sonication, [ 43 ] magnetic stirring and ball milling [ 44,45 ] and planetary centrifugal mixing and three‐roll milling. [ 46 ]…”
Section: Introductionmentioning
confidence: 99%
“…These types of dispersion procedures are required because they promote the dispersion of nanofillers from an agglomerated state to a homogeneous state. The most commonly used dispersion methods are sonication, [39,40] three roll milling, [41] planetary mixer, [42] mechanical stirring and sonication, [43] magnetic stirring and ball milling [44,45] and planetary centrifugal mixing and three-roll milling. [46] From the above studies, it was observed that the combined effect of the low-filler concentration of alumina nanoparticles and the graphene nanoplatelets for the improvement of physical and mechanical properties of the composites were not yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic fibers are known for its light‐weight and considerable stiffness. [ 1–3 ] Future trends are focusing on hybrid composite materials with nanoparticles as filler material that can replace traditional materials used in industries. [ 4 ] A detailed study on relevant literature reveals the proper material selection and research gap to develop hybrid polymer composites with synthetic fibers as reinforcement with suitable filler material that can enhance the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The studies concluded that mechanical, thermal, and structural properties of epoxy adhesives were improved based on the type of the reinforced particles. [4][5][6][7][8] Apart from these common particles, the use of various boron compounds such as boron nitride (BN) has gained importance in recent years. 9 BN, which has a two-dimensional and sp 2 configuration, is highly similar to graphite in terms of its structure, and to graphene in terms of its allotropic form.…”
Section: Introductionmentioning
confidence: 99%